Novel phosphine sulphide gold(i) complexes: topoisomerase I inhibitors and antiproliferative agents. Issue 23 (28th May 2020) - Martín-Encinas, Endika; Conejo-Rodríguez, Verónica; Miguel, Jesús A.; Martínez-Ilarduya, Jesús M.; Rubiales, Gloria; Knudsen, Birgitta R.; Palacios, Francisco; Alonso, Concepción
Abstract : Gold(i ) increases the cytotoxicity of phosphine sulfide quinolines against cancer cell lines, while heterocycles maintain the TopI inhibitory activity. Abstract : This work describes the synthesis of the gold(i ) complexes of phosphine sulphides. The formation of these new derivatives has been confirmed by X-ray crystallography. The coordination of gold(i ) with the sulphur atom of the phosphine sulphides favors the inhibition of topoisomerase I as well as a high cytotoxicity of the gold(i )-complexed compounds against the cancer line A549 with IC50 values in the nanomolar range and IC50 values below 5 μM against the SKOV3 cell line. It should be noted that the cytotoxicities observed for the new gold(i ) complexes are higher than those observed for phosphine sulphide ligands before binding to gold. Furthermore, the results also indicate that the presence of a nitrogenated heterocycle, such as tetrahydroquinoline or quinoline, is also necessary for the TopI inhibition to be maintained. In addition, no toxicity was observed when the non-cancerous lung fibroblast cell line (MRC5) was treated with the new phosphine sulphide gold(i ) complexes prepared.